Staphylococcus coagulase negativo como agente de mamite em rebanhos bovinos leiteiros da região sul do estado de Minas Gerais - Livia Lima dos Santos (2008)
This research was aimed to identifying the coagulase negative Staphylococcus (SCN) diversity involved in the clinical and subclinical inflammatory processes of the bovine mammary gland and to draw the profile of the isolated agent susceptibility. 120 SCN were isolated from 35 dairy flocks belonging to the south area of Minas Gerais State - Brazil. The clinical and subclinical mastitis diagnosis were available by strip cup and California Mastitis Test. Milk samples were collected aseptically for bacteriological analyses and somatic cells counting in tank through flowcytometric. Index bass of clinical mastitis were verified in the flocks (3,3%) caused by SCN. The species of SCN were identified by biochemistries methods and the susceptibility tests by diffusion disks with 19 antibiotics. Staphylococcus hyicus was the most frequent (15%). The susceptibility tests revealed 100% of sensibility to the danofloxacin, enrofloxacin and florfenicol. Of the appraised samples, 33 of them (27,5%) were resistant to the penicillin, 25 (20,8%) to the streptomicin, 22 (18,3%) to the ampicilin and 17 (14,2%) to the tetraciclin. The percentile of multiresistent revealed by the isolated of SCN in the studied samples is not preoccupying, position that most of the samples is sensitive to the available antibiotics in the market.